Molecular mobility and physical ageing of plasticized poly(lactide). Issue 4 (23rd June 2014) - Dobircau, Larisa; Delpouve, Nicolas; Herbinet, Romuald; Domenek, Sandra; Le Pluart, Loïc; Delbreilh, Laurent; Ducruet, Violette; Dargent, Eric
Abstract : Molecular mobility and physical ageing of amorphous plasticized polylactide (PLA) with two different contents of mesolactide are studied with the help of thermal analysis. Used plasticizers are acetyl tributyl citrate (ATBC) and triacetin (TA), two molecules with established miscibility and plasticizing efficiency. Lower plasticizer permanence of TA compared with ATBC is found. The plasticizer molecules decreased the size of the cooperativity domains at the glass transition temperature T g and likely in the glassy state by decreasing intermacromolecular interactions and notwithstanding the mesolactide content of PLA and the chemical identity of the plasticizer. The recovery function is given and shows a significant effect of the plasticizer on the physical ageing. The supplementary free volume brought by the plasticizer enhances molecular mobility in the glassy state and increases structural relaxation at one order of magnitude. The comparison between different plasticizers reveals that the structural relaxation is however independent from the type of plasticizer and the percentage of mesolactide in PLA. POLYM. ENG. SCI., 55:858–865, 2015. © 2014 Society of Plastics Engineers